The Heterogeneity of Speed of Adjustment Capital Structure Across Industrial Sectors - Robiatun, Bibit; Witiastuti, Rini Setyo (Universitas Negeri Semarang, 2021)
This study aims to analyze heterogeneity of speed of adjustment on basic industry, consumer goods, and misceleeneous companies. The population in this study uses basic industry, consumer goods, and miscellenoeus companies listed on the Indonesia Stock Exchange in 2009-2018 period. The method of determining the sample using a pusposive sampling technique based on criteries determined by researchers. We employ two-step partial adjustment model and use measure of book leverage and firm characteristic; profitability, size, tangibility, and growth which has an influence leverage target to estimate speed of adjustment. For three industries, there is evidence of heterogeneity of speef adjustment. The result showed that speed of adjustment 24% of basic industry, 37.1% of consumer goods, and 27.3% of miscellaneous industry.